Role of Ayurveda in the Management of Endometriotic Cyst: A Case Report - Khushboo Jha (Journal of Ayurveda Campus, 2025)
Background : Endometriosis is a condition in which cells similar to those in the endometrium, the layer of tissue that normally covers the inside of the uterus, grows outside of it. The presence of functioning endometrium (glands and stroma in sites other than uterine mucosa is called endometriosis. It is affecting the quality of life of millions of women. It is associated with a broad range of symptoms including Dysmenorrhea, Dyspareunia, inter-menstrual pelvic pain and infertility. Endometriotic cysts are a significant reproductive health issue which is contributing to infertility and chronic pelvic pain. In Ayurveda endometriosis and related conditions like endometriotic cyst can be understood through principles of rakta dhatu dushti and vata kapha imbalance. Method: 39-year-old women diagnosed with endometriotic cyst was treated with ayurvedic management following the basic principles of Ayurveda. The protocol includes shodhan (purification) through panchakarma and shaman therapies to improve uterine health. Ayurvedic medicines were given to improve the menstrual irregularities and backache. Post treatment follow up included ultrasonography to evaluate cyst size and reproductive health. Results: Following 8 months of Ayurvedic treatment and ultrasonography revealed complete resolution of the endometriotic cyst. Discussion: Through shodhana and shamana therapies address both symptomatic relief and the root causes of endometriotic cyst. Conclusion: This case study demonstrates the efficacy of an Ayurvedic approach in managing endometriotic cyst further research is recommended to substantiate findings. To explore broader applications of Ayurveda in Gynecological health further research is recommended